Comparative study on skin protection activity of polyphenol-rich extract and polysaccharide-rich extract from Sargassum vachellianum - Jesumani, Valentina (PLoS One, 2020)
Seaweed polyphenols and polysaccharide plays a broad range of biological activity. The objective of the present study was to study and compare the skin protection activity of fucoidan rich polysaccharide extract (SPS) and polyphenol-rich extract (SPP) from the seaweed Sargassum vachellianum. The skin protection activity was analyzed based on their ability to scavenge free radicals such as hydrogen peroxide and hydroxyl radicals, UV absorption potential, tyrosinase inhibition, moisture preservation, and antibacterial activity. From the results, both SPP and SPS protects the skin from UV damage. SPP showed good free radical scavenging ability, antimicrobial activity against E.coli and S. aureus and effectively absorbed the UVB and UVA rays whereas SPS hardly absorbs the UVA and UVB rays and showed weak free radical scavenging ability and no antimicrobial activity. SPS showed considerable inhibition on tyrosinase (51.21%) and had better moisture absorption (52.1%) and retention (63.24%) abilities than SPP. The results specified that both SPS and SPP have balancing potential on skin protection and suitable combinations of both could act as an active ingredient in cosmetics.